Evaluation of Antimicrobial Agents, Irrigation Solutions, and Surface Disinfection Techniques for Preventing Bacterial Contamination and Biofilm Formation on Implant Surfaces In Vitro - PS Priyadharsana; Vertika Dubey; Prabhleen Kaur; Priya Nagar; J Chethan; BB Priyanka (Journal of Pharmacy and Bioallied Sciences)
Background: Peri-implant diseases, driven by bacterial biofilms, threaten long-term implant success. This study evaluated various antimicrobial agents for preventing bacterial contamination and biofilm formation on implant surfaces. Methods: Ultraviolet radiation type C (UV-C) light, povidone-iodine (PVP-I), chlorhexidine (CHX), and hydrogen peroxide (H2O2) were tested against bacterial cultures. Log reduction values quantified bacterial population decrease. Biofilm formation was assessed using crystal violet staining and optical density at 570 (OD570) measurements. Results: UV-C and PVP-I showed the highest log reductions (3.7067, 3.6200), followed by CHX (2.9467) and H2O2 (2.3800). UV-C and PVP-I most effectively inhibited biofilm formation (OD570: 0.0600, 0.0800), followed by CHX (0.1200) and H2O2 (0.1767). Conclusion: UV-C and PVP-I demonstrated superior efficacy in reducing bacterial load and inhibiting biofilm formation, suggesting potential as valuable tools for preventing and managing peri-implant infections.